The Arctic and the future Arctic? Soundscapes and marine mammal communities on the east and west sides of Svalbard characterized through acoustic data - Llobet, Samuel M.; Ahonen, Heidi; Lydersen, Christian; Kovacs, Kit M. (Frontiers in Marine Science, 2023)
The Svalbard Archipelago, Norway, is warming rapidly, resulting in environmental change that is likely already affecting the underwater soundscape, a critical habitat feature for marine mammals. Baseline information about current sound levels is needed to monitor future changes. Fixed-location recorders were used in this study to characterize the soundscape and study the occurrence and phenology of marine mammals at two locations within Svalbard. Kongsfjorden (2017-2018), on the west coast, has already undergone vast environmental change, whereas M2 (2019-2020), on the east coast, remains more Arctic. The results of the study reveal that the soundscapes and species assemblages differed markedly west vs east. In the west, Arctic species were detected from winter to summer and migrant marine mammal species were detected occasionally through the autumn. In the east, Arctic species were detected constantly on an almost year-round basis, and a few migrant species were detected during summer. Vessels were detected more often in the west than in the east, in accordance with AIS traffic data that indicated more boat traffic in Kongsfjorden in the west than in the east of the archipelago. In terms of soundscapes, geophonies (wind, ice) were the main factors determining the sound energy at both locations. Kongsfjorden’s soundscape was characterized by glacier-melt sounds with moderate levels of anthropogenic noise and some biophonies (marine mammals). At M2, sea-ice noises shaped the soundscape, which was otherwise dominated by biophonies from Arctic marine mammals. At the east coast site there was little impact from anthropophonies (vessels). This study provides information on Svalbard’s current underwater soundscape, which is likely to be transformed in the future due to ongoing climate change, with the west coast reflecting future conditions in many Arctic regions if ship-traffic is not regulated.